Projetos educativos escolares e práticas alfabetizadoras emacipatórias: os contributos da Escola da Ponte de Portugal - Fernandes, Sônia Regina de Souza (Universidade do Vale do Rio do Sinos, 2008)
The present thesis is a result of a research carried out at Escola da Ponte in Portugal, with the title “Educative School Projects and Emancipatory Literacy Practices: the contribution of the Escola da Ponte – Portugal”. Concerning to the empirical dimension, the methodology adopted was an Ethnographic Case Study which was accomplished by means of systematic processes of observation and, in some situations, a participative observation of the daily activities at the school (fron September 2006 to February 2007). Different subjects of this project were interviewed and I analyzed documents that shape the pedagogical project of the school, documents such as: The Educational Project Fazer a Ponte and the Contract of Autonomy in addition to legal documents provided by the Portuguese Educational Department. The central point in this study is based on emancipatory projects of education as well as, on the conditions/contexts which may facilitate their existence as a part of the literacy practice on its initial dimensi
Keywords: alfabetização; educação libertadora; emancipação; escola; projetos educativos; emancipatory; liberating education; literacy; school; educational projects; Ciências Humanas